2020
DOI: 10.5530/pj.2020.12.102
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of Wild Stinkhorn Mushroom Extracts on Different Cancer Cell Proliferation and Study of Primary Metabolites

Abstract: Cancer is identified as the first or second leading cause of death in 91 to 172 countries and it is also ranked as third and fourth in an additional 22 countries 1,2 . Cancer is one of the major public health problem and the second leading cause of death in the United States 3 . It has been estimated that in 2020, 1,806,590 new cancer cases may occur in United States and among them 606,520 cancer death has been projected 3 . In India cancer is ranked as second leading cause of death in the urban area and place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…We have found ergosta-5,22-dien-3-ol and ergosta-7,22-dien-3-ol in all samples from Valdocarros II. Previous studies identified such compounds in wood-decay (xylophagous) fungus [78][79][80] . The highest abundances were found in samples #28 (from Hearth-1) and sample #9 (from Hearth-11), suggesting general fungal presence at Valdocarros with localized intensification at the largest hearths.…”
Section: Alcoholsmentioning
confidence: 99%
“…We have found ergosta-5,22-dien-3-ol and ergosta-7,22-dien-3-ol in all samples from Valdocarros II. Previous studies identified such compounds in wood-decay (xylophagous) fungus [78][79][80] . The highest abundances were found in samples #28 (from Hearth-1) and sample #9 (from Hearth-11), suggesting general fungal presence at Valdocarros with localized intensification at the largest hearths.…”
Section: Alcoholsmentioning
confidence: 99%
“…Despite their odor and strange and magnificent basidiome morphology, some species have been used by humans; some immature stinkhorns are edible (Laessø & Spooner, 1994;Kibby, 2015;Phillips et al, 2018), and some Phallus spp. compounds have even shown antiproliferative activity in cancer cells and leukemia cases (Ray et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Non-melanoma skin cancer is ranked as the 5 th most commonly occurring cancer, accounting for an estimated 1.04 million deaths in 2018, while melanoma skin cancer is the 19 th most commonly occurring cancer, and the incidences of nonmelanoma and melanoma skin cancers have been increasing in recent decades (WHO Fact sheet, 2018). Generally, several mushroom species have shown promising in vitro and in vivo abilities against cancer (Ivanova et al 2014;Blagodatski et al 2018;Ray et al 2020). Very few mushrooms have been testified to have anti-skin cancer activities such as Ganoderma lucidum, and Coriolus versicolor (Chinembiri et al 2014).…”
Section: Introductionmentioning
confidence: 99%